Pengalaman Pelajar Penghayat Kepercayaan Sunda Wiwitan Komunitas Gradasi Cirendeu Cimahi Jawa Barat - Agnes Widiana; Evi Fitaulifia; Kartikasari Kartikasari (Jurnal Iman dan Spiritualitas, 2021)
Freedom and religious rights in this nation have gone through a long phase of ups and downs; in this case, the ones that are most heavily highlighted are the adherents of local religions. Even so, local religion continues to exist amid various existing problems. One form of the problem is multiple efforts to discriminate and violate the right to religious freedom for students who follow the Sunda Wiwitan faith in Cirendeu, Cimahi, West Java. This study aims to explain the various forms of discrimination students receive from the Sunda Wiwitan faith. This study uses a qualitative method. Based on case studies and interviews, it is stated that there have been various forced attempts to change beliefs that often occur in schools; one of the fundamental criticisms is the absence of religious learning facilities according to ideas in school. So it is often the case that students with beliefs as believers are forced to take lessons according to the majority religion in the school.